2016
DOI: 10.1007/s10967-016-5036-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of 99Mo production rates from natural molybdenum in research reactors

Abstract: Molybdenum-99 is one of the most important radionuclides for medical diagnostics. In 2015, the International Atomic Energy Agency organized a round-robin exercise where the participants measured and calculated specific saturation activities achievable for the 98 Mo(n,c) 99 Mo reaction. This reaction is of interest as a means to locally, and on a small scale, produce 99 Mo from natural molybdenum. The current paper summarises a set of experimental results and reviews the methodology for calculating the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…In this process, 99 Mo is produced by the irradiation of molybdenum ( 98 Mo) in a thermal neutron flux, { 98 Mo(n,γ) 99 Mo}. The thermal (~ 0.025 eV) or epithermal (0.025-1.0 eV) neutrons produced by the fission of uranium in a nuclear reactor can be used to generate 99 Mo radionuclide by bombarding stable 98 Mo target material placed in the reactor [17,18]. In this process, the 98 Mo nuclei capture neutron and transform into 99 Mo isotope as shown in Fig.…”
Section: Neutron Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this process, 99 Mo is produced by the irradiation of molybdenum ( 98 Mo) in a thermal neutron flux, { 98 Mo(n,γ) 99 Mo}. The thermal (~ 0.025 eV) or epithermal (0.025-1.0 eV) neutrons produced by the fission of uranium in a nuclear reactor can be used to generate 99 Mo radionuclide by bombarding stable 98 Mo target material placed in the reactor [17,18]. In this process, the 98 Mo nuclei capture neutron and transform into 99 Mo isotope as shown in Fig.…”
Section: Neutron Activationmentioning
confidence: 99%
“…Several studies investigated the thermal and resonance neutrons input into the 99 Mo activation process. [16,17,21]. Ryabchikov et al [21] reported that the resonance part of the neutron spectra enhance the yield of 99 Mo significantly by increasing the effective cross-section of 98 Mo(n, γ) 99 Mo reaction from 0.14b to 0.7b.…”
Section: Neutron Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative routes can be classified as neutron activation of natural molybdenum using research reactor and irradiation of high enriched molybdenum using cyclotron. The first method is mainly developed in developing countries possessing a research reactor without proper fission- 99 Mo production facility (Blaauw et al, 2017;M Munir et al, 2019). The second method is mainly carried out in developed countries possessing a proper cyclotron for 99 Mo production.…”
Section: Development Of Novel Alumina By Solid-state Reaction For 99 mentioning
confidence: 99%
“…The advantages of nonfission 99 Mo compared to fission 99 Mo are the easy handling of the waste, the low radioactivity waste, and the simple post-irradiation method. On the other hand, the drawback is the low specific activity compared to fission 99 Mo (Blaauw et al 2017;Marlina et al 2017).…”
Section: Development Of New Materials Formentioning
confidence: 99%